Global-software development lifecycle: an exploratory study - Wee, Alvin Yeo (ACM New York, NY, USA, 2001)
This study was conducted to explore the efficacy of the global-software development lifecycle (global-SDLC), which comprises design, implementation and usability evaluation phase. A spreadsheet was adapted using the global-SDLC process to accommodate a number of cultures. The design and implementation phases were efficacious. However, in the usability evaluation phase, the usability evaluation techniques were only efficacious when participants, who were experienced computer users and participants who were familiar with the experimenter, were employed. Explanations, from cultural literature such as Hofstede, are presented and implications of these findings on the usability evaluation phase and the global-SDLC are also described.